Panic During COVID-19 Pandemic! A Qualitative Investigation Into the Psychosocial Experiences of a Sample of Indian People - Sharma, Gagan Deep; Ghura, Amarpreet Singh; Mahendru, Mandeep; Erkut, Burak; Kaur, Tavleen; Bedi, Deepali (Frontiers in Psychology, 2020)
The outbreak of Covid-19 has spread to the entire world and is severely affecting social psychology. We conducted semi-structured interviews on fifty-nine subjects from India to investigate the impact of information, misinfodemics (spread of wrong information), and isolation on their psychology. We perform qualitative analysis on the data. Our findings reveal that flow of information leads to anxiety, caution, and knowledge; while misinfodemics cause panic, distrust, and confusion; and isolation creates cognitive dissonance (the state of having inconsistent thoughts, beliefs, or attitudes) and adaptability among masses. The encouraging part of our findings is that, as of now, the situation is far from the state of depression. Practically, our research calls upon the government to support the masses in fighting through the crisis by focusing on pointed psychological counseling. We contribute theoretically to the body of knowledge in the field of social psychology, which is studying the psychological interventions to avoid panic amid pandemic. Future researchers in the area would do well by detailing the psychological interventions required to contain the negative impacts of the pandemic on social psychology.